Inclusive education as a technical problem - Ocampo González, Aldo (2022)
This work analyzes the technical problem in which the discourse of inclusive education has become through the lack of ethical responsibility of educational provision, a liberal argument that reinforces the permanent defense of rights while the conditions of oppression and domination conceived in terms of injustice continue to operate strongly in the life of each person and community. The objective of this work is to document how educational policies, knowledge production and teacher training, put on the rhetorical costume of the special or rather, the neo-special, to justify the sense of the inclusive. Although the special is a form of inclusion, inclusion is not necessarily a form of the special, it is a cultural revolution, a space for the production of other worlds, of fracture and permanent challenge of pedagogical knowledge. The lack of analytical rigor of these educational policies and intellectual decisions makes them unable to get rid of the problem of gender, race, multiculturalism and interculturality in the school from an individual, oppressive and negative perspective of difference. Inclusive education must think along with the zone of not-being its problems and, with it, consolidate a pragmatics that benefits the vital experience of subalternity. It is an attempt to escape the analytical monologism and monocentrism turned into pseudo-practices and resistance consciousnesses to transform the world. The subjects in the zone of non-being live in their own body and in their consciousness the experience of oppression and domination, there is a code of regulation that we must unlock so that inclusion and justice formats can dislocate the institutionalized forms of brakes on self development. The technical dimension of the inclusive argument reinforces the ontological problem of social groups, that is, a corpus of arguments enthroned through classical humanism in which difference adds a negative attribute linked to the identity of each being and adherence collectivity. The ontological policy of inclusive education consists of producing a system of reappropriation of the forces of singularization and their futures, without paying attention to the symbolic complexity of each being, inaugurating a corpus of public policies that do nothing but reproduce an effect of assimilation and a multicategorical problem to justify its task around the passive signifiers of inclusion. It concludes by identifying the need to offer a positive understanding of the difference that points to the individual plurality of each being to overcome the rhetorical and pragmatic presence of diversity as an index of assimilation in the intimacy of schooling conditions.